Religion and the rise of history : Martin Luther and the cultural revolution in Germany, 1760-1810 - Smith, Leonard S. (Leonard Sander), 1932- (James Clarke & Co, 2010)
This is the first intellectual history to study the ideal-type of model-building methodology of Otto Hintze (1861-1940) to Western historical thought and to suggest that Martin Luther also held to a way that was deeply incarnational, dynamic, and/or 'in-with-and-under'. This dual vision and 'a Lutheran ethos' strongly influenced Leibniz, Hamann, and Herder, and was therefore a matter of considerable significance for the rise of a distinctly modern form of historical consciousness in Protestant Germany. Smith's essay suggests a new time period for the formative age of modern German thought, cul.